Financial Payback Analysis of Small Wind Turbines for a Smart Home Application in Istanbul/Turkey - Ugur, Enes; Elma, Onur; Selamogullari, Ugur Savas; Tanrioven, Mugdesem; Uzunoglu, Mehmet (IEEE, 2013)
Small-scale wind turbines are promising renewable energy devices driven by the aim of carbon savings at energy generation. However, the use of small-scale wind turbines in residential areas is still very narrow because of low wind speeds, high turbulence intensity, and the perception of high aerodynamic noise produced by wind turbines. Furthermore, their high cost make it essential to assess the turbines carefully before deciding to purchase so that the optimum performance and costs can be obtained. In this study, power curves of best-selling small scale wind turbines in Turkey are compared using experimentally collected one year wind data for the use in a smart home environment at Davutpasa Campus, Istanbul. The total annual energy production of the wind turbines and financial payback periods are calculated. With the results of performed analysis, it is possible to define the most profitable small wind turbine to be used in related applications in Istanbul and in areas where wind speed is similar.
Keywords: small wind turbine; smart home; financial payback; annual energy yield; wind speed; Energy & Fuels